Gender differences in the scientific production of education in Latin America: a bibliometric study - Zahn Muñoz, Cristian (2025)
This work analyzes the presence of women in scientific productivity in indexed Latin American education journals using bibliometric methods. The study focuses on articles published in SCOPUS between 2018 and 2022. The research reveals gender differences in the field of education, examining patterns of scientific production, collaboration, and associativity, as well as differences in the impact of scientific output. The findings indicate that, compared to other fields, education in Latin America shows a smaller gender gap in scientific productivity. Additionally, there is an increase in researcher collaboration and the participation of women in journal publications. However, gender biases persist, particularly in the visibility and impact of research conducted by women.